The effect of CKD on intertrochanteric fracture treated with proximal femoral nail anti-rotation: A 7-year study - Ong art Phruetthiphat (2022)
Background: Intertrochanteric fracture is one of the most burdensome osteoporotic fractures in the elderly. Chronic kidney disease is associated with sarcopenia, especially in its advanced stages and, thus may impact functional status. Combining an intertrochanteric fracture with advanced CKD may diminish results after surgical fixation. This study aims to distinguish whether CKD affects the result of intertrochanteric fracture fixation in terms of mechanical and functional outcomes. Methods: A retrospective study reviews all intertrochanteric fractures treated with PFNA fixation from 2012 to 2018. 445 patients were classified into 5 stages of CKD and divided by eGFR = 90 ml/min/1.73 m2 into CKD and non-CKD group and by eGFR = 30 ml/min/1.73 m2 into advanced CKD and non-advanced CKD group. The primary outcome was one year Harris Hip Score (HHS). Secondary outcomes were medical complications, surgical complications, and a 1-year mortality rate. Results: Harris Hip Scores (HHS) were not different between non-CKD and CKD groups (eGFR <90 mL/min/1.73 m2). However, there was a difference between non-advanced CKD and advanced CKD groups (eGFR <30 mL/min/1.73 m2) (p < 0.001). Medical complications were not different, except for sepsis in CKD stage 5 compared with stage 1 (p = 0.023). Even though AO/OTA types were more severe in the advanced CKD group, surgical complications and 1-year mortality were not different. Conclusion: Advanced stage CKD treated with PFNA fixation is associated with lower functional outcomes at one year. Sepsis is more prone to occur after surgery in CKD stage 5. Level of evidence: Level III; Retrospective cohort study.